Temperature effect on HFMD transmission in Selangor, Malaysia - Nurmarni Athirah Abdul Wahid,; Suhaila Jamaludin,; Ayuna Sulekan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Hand, foot, and mouth disease (HFMD) has become a major concern for health authorities all over the world including Malaysia. In Malaysia, it has been reported that more than fifteen thousand people were affected by this disease in the year 2016 and it is suspected that climate variables play an important role in the incidence of HFMD. Previous studies showed that HFMD disease is associated with climatic factors such as temperature, humidity, and rainfall. Hence, this paper attempts to examine the pattern of HFMD and scrutinize the effect of temperature on HFMD in Selangor from the year 2010 to 2016. Correlation analysis is conducted to measure the relationship between HFMD incidence and temperature with a lag time effect. The generalized linear model (GLM) is then carried out to determine the influence of climate variables on HFMD disease in Selangor. Our findings discovered that the weekly mean temperature is significantly associated with HFMD incidence in Selangor. A comparison between models shows that HFMD with 2 weeks lag time mean temperature is the best-fitted model of HFMD in Selangor. This result helps to lay sound evidence for the implementation of strategies to reduce the effect of climate change especially temperature towards HFMD.